Estudio del nivel de estrés del turista de la provincia de Cotopaxi. Durante la pandemia. - Landeta Naranjo, Fabricio Xavier (2023)
For the fulfillment of this project called "STUDY OF THE LEVEL OF STRESS OF TOURISTS IN THE PROVINCE OF COTOPAXI. IN PANDEMIC TIME", the tourists who visited the province of Cotopaxi during the Covid-19 Pandemic and its variants were taken as the main object of study, since the stress level of tourists is a matter of great importance because It is known that this disease directly affects or affects the physical, emotional and psychological health of people. Cotopaxi, being a province of great tourist influence, serves as a focus for the study of this variable, thus occupying fifth place after Pichincha, Guayas, Manabí and Azuay; Thus, it will be necessary to obtain a sample of the population of the province for the application of a survey, based on the levels of stress that exist, using the non-probabilistic proven formula, resulting in a total of 385 people of different sex. and ages. After this, it was considered necessary to select the main tourist attractions of this province, which were: Cotopaxi Volcano, Quilotoa Lagoon, Yambo Lagoon, and El Boliche National Recreation Area; Once the visit sites were determined, a schedule of field trips was prepared and fulfilled. To conclude with this study, the data obtained in spreadsheets of the Microsoft Excel tourism program was tabulated, to carry out the analysis and assessment according to the IMSS (Mexican Institute of Social Security) table to know the stress level of the. Based on the above, the results were obtained that the tourists who visited the province of Cotopaxi, are in a range of mild stress, with the male gender between 18 and 26 years being the most affected segment, with a score of 45.7. Therefore, they are in an alarm phase, and it is advisable to take the pertinent measures so that the level of stress does not increase during the time of the pandemic or after it.